Employment experiences of the oral health workforce in rural New South Wales: a qualitative study - Lisa Hai My Do; Yvonne Dimitropoulos; Jessica Biles; Bradley Christian; Woosung Sohn (BMC Health Services Research)
Abstract Introduction Rural oral health practitioners in New South Wales (NSW) face unique challenges related to workforce shortages, professional isolation and limited access to specialist services. Despite the critical role in delivering oral health care to rural communities, there is limited research examining the experiences of this workforce. This study aims to explore the clinical, cultural and personal dimensions of their experiences. Methods This qualitative study utilises an inductive research design and follows Braun and Clarke’s framework for thematic analysis. Virtual semi-structured interviews were conducted with five oral health practitioners working in three participating rural Local Health Districts (LHDs) in NSW. Results Four key, interconnected themes were identified: (1) workforce recruitment and retention difficulties, (2) financial challenges and inadequate rural incentives, (3) barriers to accessing professional development opportunities, and (4) limitations to specialised oral health services access. Conclusion This study highlights the complex challenges faced by rural oral health practitioners in NSW. Addressing workforce shortages, improving financial incentives, expanding CPD access and strengthening service delivery models are crucial for sustaining the rural oral health workforce. Targeted policy interventions and support systems are needed to enhance workforce retention and improve oral health access and therefore, outcomes, in rural communities.